Historical dictionary of Ukraine - Katchanovski, Ivan; Kohut, Zenon E.; Nebesio, Bohdan Y.; Yurkevich, Myroslav, 1950- (Historical dictionaries of Europe., 2013)
The Historical Dictionary of Ukraine, Second Edition covers the history of Ukraine and its struggles through a chronology, an introductory essay, appendixes, and an extensive bibliography. The dictionary section has over 700 cross-referenced entries on population, geography, economy, politics, and culture; descriptions of institutions, cultural monuments, political parties, battles and wars; and biographical sketches of key individuals in politics, the arts and sciences, the church, and the military. This book is a vital.